Current rules of the deposit guarantee system in Poland - Zawadzka, Patrycja (University of Wroclaw. Faculty of Law, Administration & Economics, 2011)
The article considers the matter of the deposit guarantee system in Poland, which is coordinated by the Bank Guarantee Fund (BFG). Presented in the first part are the organization of the BFG and its tasks, such as guaranteeing, aiding, controlling and analyzing the banking sector. Discussed in the publication are changes in Polish law, especially in the reaction to the global crisis on the financial market in the late 2000s. Finally, the future outlook for EU regulation is presented, along with a number of conclusions on the potential legislative changes in the Act on the BFG. The main goal of the article is to characterize details of the Polish implementation of Directives 94/19/EC and 2009/14/EC, as well as the actual form of the deposit guarantee system, and to answer the question of whether the Act on the BFG corresponds to the EU directives.
Keywords: Bank Guarantee Fund (BFG); Polish law